Indian teachers’ and parents’ perceptions and experiences of food and nutrition education in primary schools: mixed-method study - Wincie Wilmah, A.; Jaishree Karthiga, R. K. (Frontiers in Nutrition, 2025)
IntroductionFood and nutrition education (FNE) is vital for shaping lifelong dietary behaviours and advancing sustainable development goals related to food security and responsible consumption. Despite global initiatives, India lacks a standardized framework for FNE in primary schools, resulting in inconsistent curricula and limited teacher preparedness.MethodologyThis mixed-method study examined 350 stakeholders, including 110 primary school teachers, 187 parents, and 53 students in Tamil Nadu through structured surveys and qualitative interviews. Quantitative findings revealed that 73% of participants supported weekly FNE sessions.Results76% of teachers reported inadequate training in food processing and nutrition, and 68% preferred FNE as a standalone subject. Statistically significant differences emerged between urban and rural stakeholders in sustainability awareness (χ2 = 10.94, p < 0.01), and teacher confidence in nutrition education correlated positively with successful FNE implementation (r = 0.68, p < 0.001).AnalysisQualitative analysis identified three key themes: (1) limited institutional frameworks for sustainable FNE, (2) strong sociocultural influences on food choices, and (3) disparities in sustainability awareness across regions.DiscussionThe findings support policy-driven reforms, such as mandatory teacher training, curriculum restructuring to embed FNE, and community engagement programmes. This study contributes practical insights for education policymakers aiming to enhance children’s food and nutrition literacy and promote sustainable dietary practices across Indian primary schools.